Cologastric strictures: What is the best treatment?. Issue 1 (9th January 2017) - Lu, Richard; Brown, Kimberly; Okereke, Ikenna
Abstract: A 31-year-old gentleman who had undergone an emergent esophagectomy and reconstruction with a colon interposition graft, presented with a long-standing cologastric stricture. He had undergone multiple attempts at endoscopic dilation over multiple decades with little symptomatic relief. He underwent a resection and reconstruction of the anastomosis entirely through an abdominal approach. He did well from surgery and experienced complete symptomatic relief immediately. Complications of colon interposition grafts can occasionally be treated using an abdominal incision only.